An Arabic text as content in an Indonesian EFL setting: Trans-language - Safi Aini (Institut Agama Islam Negeri Palopo, 2020)
Maynard and Furlong (1995) state that teaching materials should be something that students can relate to, and that occupy students’ interests. They assert that teachers must recognise what students already know about material to be learnt, and introduce teaching material which students are somewhat familiar with. This study was conducted at an Islamic school where the English teachers fostered a culture of English learning using content embedded in Islamic theme. This was manifested in Arabic textbooks, which were used as a resource for learning English, and as a basis for translation and communicative language activities. The purpose of this study is to examine learners’ perceptions about the use of Arabic texts as a resource for learning English as a foreign language (EFL). The results show that through a trans-language approach, learners can improve their English vocabulary, understand parts of speech of translated English words, improve their use of English grammar, especially regarding tenses, learn how to translate, and speak English more fluently, since they understand the content of the textbooks. However, they also have difficulty in making English sentences in the passive voice, and in pronouncing English words.